Optimization of shallow Schwedler domes - Duda, Grzegorz W. (Computer Assisted Methods in Engineering and Science, 2023)
The paper deals with the optimization of regular space trusses with fixed external dimensions under uniform snow and dead-weight loading. Attempts are being made to find such a number of truss joints which minimise the material volume. The set of constraints imposed on a structure includes the effect of the loss of stability of the compressed bar. The statical problem of shallow domes including geometrical nonlinearity was solved by using the Newton-Raphson iteration procedure.